Directed Differentiation of Human Embryonic Stem Cells to Neural Crest Stem Cells, Functional Peripheral Neurons, and Corneal Keratocytes. Issue 12 (22nd August 2017) - Zhu, Qian; Li, Mingming; Yan, Chuan; Lu, Qiqi; Wei, Shunhui; Gao, Rong; Yu, Mengfei; Zou, Yu; Sriram, Gopu; Tong, Huei J.; Hunziker, Walter; Seneviratne, Chaminda J.; et al.
Abstract : Neural crest stem cells (NCSCs) are a transient and multipotent cell population giving rise to various cell types with clinical importance. Isolation of human NCSCs is extremely challenging that limits our knowledge about neural crest development and application. Here, a defined protocol to efficiently direct human embryonic stem cells (hESCs) to NCSCs and multiple neural crest lineages is presented. A unique combination of small molecule inhibitors and growth factors is employed to generate NCSCs from hESCs through a neuroectoderm stage. The self‐renewal and multipotent capacities of hESC‐derived NCSCs are assessed subsequently. In the feeder‐free system, hESC‐derived NCSCs (P75 + /HNK1 + /AP2α + /PAX6 − ) in high purity are efficiently generated following neuroectodermal restriction. They can be propagated and differentiated toward multiple neural crest lineages in vitro, such as functional peripheral neurons (β‐tubulin III + /peripherin + ), mesenchymal stem cells (CD73 + CD90 + CD105 + ), and corneal keratocytes (keratocan + ). The in vivo developmental potential of hESC‐derived NCSCs is confirmed using zebrafish embryos. This report is the first demonstration of efficient differentiation of hESCs into corneal keratocytes as a monolayer in a feeder‐free system. Considering the high efficacy of NCSC generation, this new method will be a useful tool for future clinical organ repair and regeneration, such as peripheral nerve regeneration and corneal repair. Abstract : Neural crest stem cells (NCSCs) are a transient and multipotent cell population giving rise to various cell types. In this study, the authors established a novel approach to efficiently differentiate human embryonic stem cells (hESCs) into NCSCs with in vivo developmental potential through a neuroectoderm stage, and these NCSCs could be further induced into multiple neural crest lineages such as mesenchymal stem cells, corneal keratocytes, and peripheral neurons. Considering the clinical importance of NCSCs and neural crest lineages, this new method will be a useful tool for future clinical organ repair and regeneration, such as peripheral nerve regeneration and corneal repair. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB, visitwww.afob.org .